The emerging role of long non-coding RNAs, microRNAs, and an accelerated epigenetic age in Huntington’s disease - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Ebrahimzadeh, Kaveh; Noroozi, Rezvan (Frontiers in Aging Neuroscience, 2022)
Huntington’s disease (HD) is a dominantly inherited neurodegenerative disease with variable clinical manifestations. Recent studies highlighted the contribution of epigenetic alterations to HD progress and onset. The potential crosstalk between different epigenetic layers and players such as aberrant expression of Non-coding RNAs and the methylation alterations has been found to affect the pathogenesis of HD or mediate the effects of trinucleotide expansion in its pathophysiology. Also, microRNAs have been assessed for their roles in the modulation of HD manifestations, among them are miR-124, miR-128a, hsa-miR-323b-3p, miR-432, miR-146a, miR-19a, miR-27a, miR-101, miR-9*, miR-22, miR-132, and miR-214. Moreover, long non-coding RNAs such as DNM3OS, NEAT1, Meg3, and Abhd11os are suggested to be involved in the pathogenesis of HD. An accelerated DNA methylation age is another epigenetic signature reported recently for HD. The current literature search collected recent findings of dysregulation of miRNAs or lncRNAs as well as methylation changes and epigenetic age in HD.